2021
DOI: 10.3390/ijerph18147683
|View full text |Cite
|
Sign up to set email alerts
|

The Cumulative Risk of Prenatal Exposures to Chemical and Non-Chemical Stressors on Birth Outcomes in Suriname

Abstract: The cumulative exposure to chemical and non-chemical stressors may have an impact on birth outcomes. The aim of this study is to examine the cumulative exposure of a mixture of chemicals (mercury, lead, selenium and tin) and non-chemical stressors (social support, perceived stress, probable depression and BMI) on birth outcomes (birthweight, gestational age at birth, and Apgar score at 5 min). The study population is a subset (n = 384) of the Caribbean Consortium for Research in Environmental and Occupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…In order to examine whether psychosocial work stress during pregnancy was related to the risk of giving birth to a preterm baby or a baby small for the gestational age, a study was conducted in Denmark by Larsen et al ( 13 ), but the association between work stress and preterm birth was not confirmed. However, this association was indeed found in the study by Gokoel et al ( 42 ). Likewise, Trocado et al ( 16 ) found a possible association between low birth weight and day and night rotating shifts.…”
Section: Resultssupporting
confidence: 59%
“…In order to examine whether psychosocial work stress during pregnancy was related to the risk of giving birth to a preterm baby or a baby small for the gestational age, a study was conducted in Denmark by Larsen et al ( 13 ), but the association between work stress and preterm birth was not confirmed. However, this association was indeed found in the study by Gokoel et al ( 42 ). Likewise, Trocado et al ( 16 ) found a possible association between low birth weight and day and night rotating shifts.…”
Section: Resultssupporting
confidence: 59%
“…We also acknowledge that results from our study may not be directly comparable to the NICHD Fetal Growth study, as the chemical exposures differed. An additional study of pregnant people in the Caribbean utilized a path analysis, a subset of structural equation modeling ( Gokoel et al, 2021 ). In that study, the chemical construct (comprised of mercury, lead, selenium, and tin measured in maternal whole blood) and increasing PSS and depression scores were associated with lower birthweight and gestational age ( Gokoel et al, 2021 ), which supports our findings that there is a joint effect of chemical and non-chemical stressors on fetal growth.…”
Section: Discussionmentioning
confidence: 99%
“…An additional study of pregnant people in the Caribbean utilized a path analysis, a subset of structural equation modeling ( Gokoel et al, 2021 ). In that study, the chemical construct (comprised of mercury, lead, selenium, and tin measured in maternal whole blood) and increasing PSS and depression scores were associated with lower birthweight and gestational age ( Gokoel et al, 2021 ), which supports our findings that there is a joint effect of chemical and non-chemical stressors on fetal growth. Other studies using stratified single pollutant models have shown that the relationships between increasing chemical exposures and adverse pregnancy outcomes are stronger in the presence of stress ( Padula et al, 2020 ; Aker et al, 2020 ; Ferguson et al, 2019 ; Ashrap et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%